2017
DOI: 10.1002/hbm.23495
|View full text |Cite
|
Sign up to set email alerts
|

On the dependence of response inhibition processes on sensory modality

Abstract: The ability to inhibit responses is a central sensorimotor function but only recently the importance of sensory processes for motor inhibition mechanisms went more into the research focus. In this regard it is elusive, whether there are differences between sensory modalities to trigger response inhibition processes. Due to functional neuroanatomical considerations strong differences may exist, for example, between the visual and the tactile modality. In the current study we examine what neurophysiological mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 45 publications
5
44
1
Order By: Relevance
“…This region is wellknown to play a central role in inhibitory control processes (e.g., Aron, Monsell, Sahakian, & Robbins, 2004;Bodmer & Beste, 2017;Dippel & Beste, 2015;Stock, Popescu, Neuhaus, & Beste, 2016) and has previously been shown to be associated with inhibitory gating processes reflected by the P1 during backward inhibition (Wolff et al, 2018). The larger P1 in the nth trial of the BI compared with the BASE condition therefore suggests that the suppression of the inhibitory effect of the n-1 trial on the n-2 trial is stronger in the BI condition.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This region is wellknown to play a central role in inhibitory control processes (e.g., Aron, Monsell, Sahakian, & Robbins, 2004;Bodmer & Beste, 2017;Dippel & Beste, 2015;Stock, Popescu, Neuhaus, & Beste, 2016) and has previously been shown to be associated with inhibitory gating processes reflected by the P1 during backward inhibition (Wolff et al, 2018). The larger P1 in the nth trial of the BI compared with the BASE condition therefore suggests that the suppression of the inhibitory effect of the n-1 trial on the n-2 trial is stronger in the BI condition.…”
Section: Discussionmentioning
confidence: 89%
“…ICA, infomax algorithm), which was used to correct blinks, pulse artifacts, and vertical eye-movements. By means of this transformation, it is possible to identify electrodes which best reflect ERP-component reflecting relevant cognitive neurophysiological subprocesses(Bodmer et al, 2018;Bodmer & Beste, 2017;Kamarajan, Pandey, Chorlian, & Porjesz, 2015;Kayser & Tenke, 2015a). For trials comprising correct responses, cue-locked segments were formed for all conditions separately.…”
mentioning
confidence: 99%
“…Interestingly, interactive effects in line with the behavioral data were obtained for the C-cluster in the window between~210 and 380 ms. We observed that MPH modulates the onset latency and the amplitude of the C-cluster, specifically, in the most demanding FL conflict condition. The C-cluster has been suggested to reflect stimulus-response mapping or the decision process between stimulus evaluation and responding (Verleger et al, 2014;Wolff et al, 2017) and has previously been shown to be associated with functions of the left inferior and superior parietal lobes (BA40 and BA7) (Bodmer & Beste, 2017;Wolff et al, 2017). No such drug effects were evident in the remaining experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the high baseline group, no such differences between compatible and incompatible Nogo trials were observed. Previous data has already suggested that BA7 and BA39 are involved in inhibitory control when these processes are modulated by perceptual conflicts (Bodmer & Beste, 2017). Moreover, inhibitory control relates to the detection of a response conflict (Klein, Petitjean, Olivier, & Duque, 2014;Stürmer, Siggelkow, Dengler, & Leuthold, 2000;Tandonnet, Garry, & Summers, 2011;Taylor, Nobre, & Rushworth, 2007;Verleger, Kuniecki, Möller, Fritzmannova, & Siebner, 2009).…”
Section: Resting Theta Activity Groupingmentioning
confidence: 97%
“…However, as mentioned above, evidence indicates that successful response inhibition performance is associated with elevated (event-related) theta band activity Dippel et al, 2016, 2017Huster et al, 2013Liu et al, 2014;Müller et al, 2017;Vahid et al, 2018). The reason is that superior prefrontal areas are well-known to be an important structure in a cortical network subserving inhibitory control (Bari & Robbins, 2013;Hung, Gaillard, Yarmak, & Arsalidou, 2018;Obeso et al, 2017;Xu et al, 2017), and that parietal regions become involved when conflicting sensory information modulated behavioral control (Adelhöfer et al, 2018;Bodmer & Beste, 2017;Fokin et al, 2008;Gothelf et al, 2007;Ocklenburg, Güntürkün, & Beste, 2011;Takeichi et al, 2010). Based on this, it is conceivable that there are stronger effects of conflicting information during inhibitory control in the low baseline and low modulation groups compared to the high baseline and high modulation groups at the behavioral and neurophysiological level.…”
mentioning
confidence: 99%